Peningkatan Kompetensi Guru KKG Wiradadaha 1 dalam Pengembangan Media Ajar Digital Berbasis STEAM melalui Pelatihan dan Pendampingan Terstruktur - Nuk Ghurroh Setyoningrum; N. Nelis Febriani SM; Anisa Solehah Nurwendah; Pepi Alpiani; Kholiq Mochamad Ramdan; Putri Khozizah (JURPIKAT, 2026)
The community service program was initiated due to the limited educational technology skills and lack of variation in digital learning media used by teachers in the Wiradadaha 1 Teacher Working Group, Tasikmalaya. These conditions hinder the optimal implementation of project-based learning aligned with 21st-century competencies. This program aims to enhance teachers’ abilities in developing digital learning media based on Science, Technology, Engineering, Arts, and Mathematics (STEAM) through structured training and mentoring. The methods included material presentation, demonstration, guided practice, and technical assistance in designing storyboards and producing digital media. The results indicate a significant improvement in participants’ competencies in creating creative, interactive, and STEAM-oriented learning media. This program has contributed positively to teachers’ readiness to integrate educational technology and is recommended for continuation through sustained mentoring initiatives.